Olfactory Mucosa Mesenchymal Stem Cells Ameliorate Cerebral Ischemic/Reperfusion Injury Through Modulation of UBIAD1 Expression - Liu, Jianyang; Huang, Yan; He, Jialin; Zhuo, Yi; Chen, Wei; Ge, Lite; Duan, Da; Lu, Ming; Hu, Zhiping (Frontiers in Cellular Neuroscience, 2020)
Mesenchymal stem cells have presented a promising neuroprotective effect in cerebral ischemic-reperfusion (I/R). Olfactory mucosa mesenchymal stem cells (OM-MSCs), a novel source of MSCs located in the human nasal cavity, are easy to obtain and situated for autologous transplantation. The present study was designed to evaluate the neuroprotective effects of OM-MSCs on cerebral I/R injury and the possible mechanisms. In the transient middle cerebral artery occlusion (t-MCAO) model, excessive oxidative stress and increased swollen mitochondrial were observed in the peri-infarct cortex. Intravenous injection of OM-MSCs ameliorated mitochondrial damage and restored oxidant/antioxidant imbalance. Using oxygen glucose deprivation/reperfusion (OGD/R) model in vitro, we discovered that the exposure of mouse neuroblastoma N2a cells to OGD/R triggers excessive reactive oxygen species generation, and induces mitochondrial deterioration with decreased mitochondrial membrane potential, and reduced ATP content. OM-MSCs transwell coculture attenuated the above perturbations accompanied with increased UBIAD1 expression, whereas these protective effects of OM-MSCs were blocked when UBIAD1 was knocked down. UBIAD1-sepecific siRNA reversed the increased membrane potential and ATP content promoted by OM-MSCs. Additionally, UBIAD1-sepecific siRNA blocked the oxidant/antioxidant balance treated by OM-MSCs. Overall, our results suggested that OM-MSCs exert neuroprotective effects in cerebral I/R injury by attenuating mitochondrial dysfunction and enhancing anti-oxidation via upregulation of UBIAD1.